KAJIAN BIOLOGI REPRODUKSI KERAPU MACAN (EPINEPHELUS FUSCOGUTTATUS) DI PERAIRAN LABANGKA KABUPATEN SUMBAWA: Reproductive Biology Study of Tiger Grouper (Epinephelus Fuscoguttatus) In Labangka Waters, Sumbawa District - Adniati Handayani; Evron Asrial; Luh Gede Sumahiradewi; Ni Kadek Puji Astuti (Yayasan Al-Amin Qalbu, 2023)
Tiger grouper is a type of fish whose habitat is in waters, especially rocky waters with a water depth of about 0.5-3 cm (young) and 7-40 cm (adults) from the surface. Tiger grouper is caught with bottom line and net. The purpose of this study was to determine growth parameters regarding growth patterns and condition factors, and to determine reproductive biology parameters regarding gonads, eggs and ﬁcundity of tiger grouper. This study used a dependent descriptive survey method which was carried out in Labangka waters, Sumbawa Regency. Data analysis used simple regression analysis. The results of data processing showed a positive LWR (length weight relationship) pattern (ln W = -a + b ln L) and a hyper-allometric growth pattern (b>3) with a value of b = 3.6. While the value of the condition factor is K average = 1.41 where the K value obtained indicates that the body of the grouper fish in Labangka is less flat and fleshy and is still in its infancy. The results of fecundity data processing produced 675,073.34 eggs/gonads with a gonad weight of 30 g, a gonad length of 8.8 cm and a parent fish weight of 489 g and a length of 29.8 cm